Assessing the Supression on Weeds by Cover Plants in Amazonas, Brazil - Leandro Amorim Damasceno; José Eduardo Borges Carvalho; Francisco Alisson Xavier; Ansselmo Ferreira dos Santos; Gerlândio Suassuna Gonçalves; Alan Ferreira Leite de Lima; Wildson Benedito Mendes Brito; Cláudio Luiz Leone Azevedo; José Ferreira da Silva (Cutting-edge Research in Agricultural Sciences Vol. 10, 2021)
The productivity of citrus plants has not reached its maximum potential due to the action of several factors that directly affect agricultural profitability. Among these factors, weed interference has a great importance since it causes a reduction in crop productivity. Technological limitations and inadequate management of orchards are threats to the sustainability of the crop. Compaction and erosion have motivated some field studies to assess weed management alternatives in the crop interrow, such as the use of cover plants to minimize losses, exploiting more rationally the natural resources. The aim of this study was to assess the effect of different cover crops on suppression of weeds in an orange orchard. The research was conducted in a commercial orange production area located in Rio Preto da Eva, AM, Brazil. The experimental design was a randomized block design with six treatments and four replications. Treatments were control, millet, jack bean, forage turnip, brachiaria, millet + jack bean. The evaluated characteristics were weed density, soil cover percentage, total weed dry matter, total cover plant dry matter and growth indices (leaf area index, leaf area ratio, and specific leaf area). Cover plants provided a good dry matter production and had a suppressive effect on weed growth, except for forage turnip. Brachiaria and jack bean presented the highest values of leaf area index and leaf area ratio. Cover plants suppressed weed growth in relation to the producer management, except for the forage turnip.